2009
DOI: 10.1161/circheartfailure.108.811539
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Defects in Intracellular Calcium Cycling in Whole Failing Rat Heart

Abstract: Background-A number of defects in excitation-contraction coupling have been identified in failing mammalian hearts.The goal of this study was to measure the defects in intracellular Ca 2ϩ cycling in left ventricular epicardial myocytes of the whole heart in an animal model of congestive heart failure (CHF). Methods and Results-Intracellular Ca 2ϩ transients were measured using confocal microscopy in whole rat hearts from age-matched Wistar-Kyoto control rats and spontaneously hypertensive rats at Ϸ23 months of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 31 publications
3
48
0
Order By: Relevance
“…An interesting implication of these results is that RAN could be antiarrhythmic in the settings of ischemia and congestive heart failure where the vulnerability to calcium alternans is also increased (Kapur et al, 2009a;Wasserstrom et al, 2009;Wilson et al, 2009) and where enhanced late I Na has been demonstrated (Maltsev et al, 2001(Maltsev et al, , 2007Undrovinas et al, 2002Undrovinas et al, , 2006Valdivia et al, 2005), although a link between these two effects remains to be investigated. Finally, it is important to note that RAN also blocks human ether a-go-go-related gene channels and thus might induce some of its electrophysiological actions independently from the blockade of I Na,L .…”
Section: Ran Blocks Effects Of Late I Na On Cardiac Calcium Cycling 389mentioning
confidence: 96%
“…An interesting implication of these results is that RAN could be antiarrhythmic in the settings of ischemia and congestive heart failure where the vulnerability to calcium alternans is also increased (Kapur et al, 2009a;Wasserstrom et al, 2009;Wilson et al, 2009) and where enhanced late I Na has been demonstrated (Maltsev et al, 2001(Maltsev et al, , 2007Undrovinas et al, 2002Undrovinas et al, , 2006Valdivia et al, 2005), although a link between these two effects remains to be investigated. Finally, it is important to note that RAN also blocks human ether a-go-go-related gene channels and thus might induce some of its electrophysiological actions independently from the blockade of I Na,L .…”
Section: Ran Blocks Effects Of Late I Na On Cardiac Calcium Cycling 389mentioning
confidence: 96%
“…Furthermore, RyR2 R4496C hearts showed significantly lower alternans ratio and alternans duration at each stimulation frequency between 10-14 Hz (Fig.2C, D (40,55,57). It is thought that SCR necessitates and facilitates the occurrence of Ca 2+ alternans (25,28,38,(41)(42)(43)(44)(45)(46). Hence, it is of interest to determine whether SCR is involved in the occurrence of Ca 2+ alternans in intact working RyR2 R4496C mutant hearts.…”
mentioning
confidence: 96%
“…[7][8][9][10][11] There are multiple problems that could lead to Ca 2ϩ cycling defects at the level of Ca 2ϩ release from the sarcoplasmic reticulum (SR), 9 but one of the first recognized and among the most important was a decrease in expression of the Ca 2ϩ -sensitive ATPase in the SR. This protein is responsible for Ca 2ϩ reuptake into SR and thus serves as the main mechanism for clearance of Ca 2ϩ from the cytoplasm, which then terminates systole and initiates diastole.…”
Section: How Does Calcium Dysregulation Results In Ventricular Arrhythmentioning
confidence: 99%